2008
DOI: 10.1111/j.1469-7580.2007.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

A method to establish the relationship between chronological age and stage of union from radiographic assessment of epiphyseal fusion at the knee: an Irish population study

Abstract: Characteristic changes during epiphyseal union provide a skeletal age, which when compared with age-based standards provides an estimation of chronological age. Currently there are no data on epiphyseal union for the purposes of age estimation specific to an Irish population. This cross-sectional study aims to investigate the relationship between stage of epiphyseal union at the knee joint and chronological age in a modern Irish population. A novel radiographic method that sub-divides the continuum of developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 14 publications
10
83
0
2
Order By: Relevance
“…Despite the persistence of this feature being reported in multiple anatomical regions [25][26][27][28], the general consensus within the literature has been that following the completion of epiphyseal fusion, epiphyseal scars will become obliterated, resulting in a lack of distinction between the diaphysis and epiphysis when observed radiographically [5,16,17,28,29]. As a result of this perception, the transition between an observable epiphyseal scar and its disappearance has been incorporated into the staging criteria of several methods of age estimation [30][31][32]. There is however a paucity of published literature in relation to the potential persistence of the epiphyseal scar in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the persistence of this feature being reported in multiple anatomical regions [25][26][27][28], the general consensus within the literature has been that following the completion of epiphyseal fusion, epiphyseal scars will become obliterated, resulting in a lack of distinction between the diaphysis and epiphysis when observed radiographically [5,16,17,28,29]. As a result of this perception, the transition between an observable epiphyseal scar and its disappearance has been incorporated into the staging criteria of several methods of age estimation [30][31][32]. There is however a paucity of published literature in relation to the potential persistence of the epiphyseal scar in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is an obvious lack of standards for epiphyseal union for the purposes of assignment of chronological age 18 . Therefore, interpretation is likely to vary among investigators within different countries; this may be explained, however, on the basis of how the authors have classified their range of union 13 . It is generally accepted that there was no difference in the stage of union of the various epiphyses between right and left sides, which indicates that epiphyseal union appears to occur at the same time on both sides 13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…This study has noted that there is generally a difference of two years between males and females, which is in agreement with the results of previously published studies, which have found that females typically develop union approximately two years in advance of males 16,20,24,25,34,35 . Therefore, it is clear that separate age range standards are required for males and females to ensure the greatest accuracy of age estimation 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should be apparent in at least one view on the radiograph, as a continuous radiolucent gap between the epiphysis and diaphysis. [14,15] Stage 1 -Beginning union: The epiphyseal and diaphyseal surfaces closely move towards each other. There is a narrow radiolucent strip between adjacent surfaces of the epiphysis and diaphysis when compared to the state of non-union.…”
Section: Methodsmentioning
confidence: 99%